Simultaneous Estimation and Validation of Paracetamol, Aceclofenac and Chlorzoxazone by HPLC in Pure and Pharmaceutical Dosage Form - Hari Krishnan, N.; Gunasekaran, V.; Roosewelt, C.; Kalaivani, K.; Chandrasekaran, S.; Ravichandiran, V. (Asian Journal of Chemistry, 2010)
A simple, accurate, precise and reproducible high performance liquid chromatographic method has been developed for the simultaneous estimation of paracetamol, aceclofenac and chlorzoxazone in pharmaceutical dosage forms. A Phenomenex ODS C18 column (250 mm × 4.6 mm i.d., 3-5 mcm particle size) in gradient mode, with mobile phase acetonitrile and orthophosphoric acid (40:60) (v/v), the flow rate was 1 mL/min and effluent was monitored at 275 nm. The approximate retention time for paracetamol, aceclofenac and chlorzoxazone were 2.176, 4.003 and 5.513 min, respectively. The linearity for paracetamol, aceclofenac and chlorzoxazone was in the range of 10-100, 2-20 and 10-100 mcg/ mL, respectively. Quantity found for paracetamol, aceclofenac and chlorzoxazone were 517.36, 103.16 and 517.76 mg, respectively. The percentage estimation of labeled claims of paracetamol, aceclofenac and chlorzoxazone from marketed tablet was found to be 103.47, 103.16 and 103.55, respectively. The method was validated in terms of accuracy, precision, specificity, ruggedness and robustness. The addition of known quantity of standard drugs in the pre-analyzed test solution and percentage recovery was calculated in each case carried out the recovery studies. The percentage recoveries obtained for paracetamol, aceclofenac and chlorzoxazone were found within the range of 97.27 -102.00 %. The proposed method is found to be accurate, precise, simple and rapid which can be used routinely for simultaneous estimation of proposed combination in tablet formulation.